SEGMENTASI CITRA DENGAN HISTOGRAM THRESHOLDING MENGGUNAKAN ANALISIS CLUSTER HIRARKIS - Rizki Rizkyatul Basir (Institut Bisnis Muhammadiyah Bekasi, 2020)
Object segmentation in the image aims to separate the object area from the background area. Before the segmentation process, the image undergoes some initial processing to obtain good object segmentation results. Pre-processing is an image processing operation to improve image quality. An image histogram is a graph depicting the quantitative distribution of the value of the degree of gray pixels in or a certain part of the image. From the table we can see the comparison of the values for thresholding of the 4 methods used in image testing image 1 gets the best results with a value of 59, image 2 with a value of 105, image 3 with a value of 161, image 4 with a value of 121 and image 5 with a value of 102 and from the table value it can be seen that the proposed method gives better ME values than the 3 methods another (otsu, KI, Kwon).